Expression of connexin genes in hippocampus of kainate-treated and kindled rats under conditions of experimental epilepsy - Söhl, Goran; Güldenagel, Martin; Beck, Heinz; Teubner, Barbara; Traub, Otto; Gutiérrez, Rafael; Heinemann, Uwe; Willecke, Klaus (Brain research. Molecular brain research., 2000)
We have analyzed whether the expression of connexin genes is altered in the hippocampus of kindled and kainate-treated rats, i.e., animal models of human temporal lobe epilepsy. We have tested this hypothesis by analyzing mRNA, protein abundance and cellular location of connexins (Cx) 43, 36, 32 and 30. The expression of glial fibrillary acid protein and mRNA was also monitored both in kainate-treated and kindled rats, in order to take into account reactive gliosis under these conditions. We found significantly increased expression of GFAP mRNA (100%) and protein (178%) in kainate-treated rats 4 weeks after kainate application, whereas in kindled rats only moderate increases of GFAP mRNA and protein were detected 2–3 weeks (group 2) or 4–6 weeks (group 1) after the last stage 5 induced seizure. Under gliotic conditions, connexins 43 and 30 mRNA or protein expression in astrocytes of kainate-treated rats were nearly unaffected. Cx36 mRNA expression (presumably in neurons) was significantly reduced (44%), whereas abundance of Cx36 protein was only slightly reduced. In both groups of kindled rats, Cx30 and Cx43 mRNA or protein expression were either slightly decreased or unchanged. Again, Cx36 mRNA and protein expression were reduced by about half in group 2. Immunofluorescence analysis of Cx43, Cx36 and Cx30 expression revealed that 4 weeks after the last kainate administration or kindling, cellular localization of these connexins was indistinguishable from control animals.